Immunohistochemical study of thrombomodulin expression in multiple organs dysfunction syndrome - Luo, Si-min (Zhongguo wei zhong bing ji jiu yi xue = Chinese critical care medicine = Zhongguo weizhongbing jijiuyixue, 2003)
OBJECTIVE: To study the expression of thrombomodulin (TM) and its significance in the pathogenesis of multiple organs dysfunction syndrome (MODS)